“Is ethical eating a matter of belief”: Activating organic food consumption with curvilinear impacts of religious beliefs - Cong Doanh Duong; Thi Thanh Hoa Phan; Thu Van Bui; Trong Duc Tran; Nhat Minh Tran (Acta Psychologica)
Although environmental sustainability has become a growing priority, the role of religious convictions in shaping pro-environmental consumption—particularly in relation to organic food—remains underexplored. This gap is especially evident in non-Western contexts, where cultural and religious values may significantly influence consumer behavior. This research utilized the Norm Activation Model to explore the effect of religious beliefs —karmic beliefs, afterlife beliefs, and beliefs in a just world—on organic food consumption through the activation of personal (moral) norms. Using data collected from a sample of 5326 Vietnamese consumers, the findings indicate that karmic beliefs, afterlife beliefs, and beliefs in a just world individually and collectively enhance personal moral norms, which in turn positively influence organic food purchase intentions and behaviors. Furthermore, ascription of responsibility and awareness of consequences significantly affect purchase intentions and behaviors. The study contributes to a deeper understanding of how moral norms mediate the influence of religious beliefs on sustainable consumer behavior and identifies key psychological drivers that can bridge the intention–behavior gap in organic food consumption. This study offers insights into promoting organic food consumption by incorporating religious and ethical values into consumer engagement strategies.